STRATEGI PENGEMBANGAN PEMASARAN BUAH MANGGA ARUMANIS 143 PT. TRIGATRA RAJASA SITUBONDO JAWA TIMUR - Fitranto, Rachmat; Dwi Wahyono, Nanang; Wibisono, Yossi (Jurnal Agribisnis Indonesia, 2020)
Indonesian has been ranked as 5th mango producer in the world with total production reached 2.18 million, however, Indonesian has not included the top ten world mango exporter countries. Indonesian total export was 1,240 tons and only fulfilled 0,6% of the world export value. PT. Trigatra Rajasa is one of the Arumanis 143 mango producers in Indonesian. The research objective was to analyze internal and external factors which influence marketing mango of PT Trigatra Rajasa including the arrangement of strategic recommendation to incline market value. Data collection was done from January to May 2019 through observation and respondent interview. Questioner with SWOT (Strengths, Weaknesses, Opportunities, Threats)and QSPM (Quantitative Strategic Planning Matrix) method was used during the interview. Analysis tools such as IFE, SWOT and QSPM were utilized in this research. The result showed that IFE (internal factor evaluation matrix) and EFE (external factor evaluation matrix) calculation matrix were given total score 2,85 and 2,8, respectively. Adding result of both matrix was positioning the mango marketing reality of PT Trigatra Rajasa in compartment V, mean hold and maintain. In this compartment, market penetration and product development strategy were suggested to be applied. Market penetration was recommended strategy to increase marketing of mango PT. Trigatra Rajasa based on QSPM (4,03) and efficiency of production budget through the utilization of mechanization (3,00) were suggested.